The Influence of Human Resource Competence and Organizational Commitment on The Performance of International Cooperation Projects (A Study at The Directorate General of Advanced Healthcare, Ministry of Health of The Republic of Indonesia) - Cep Rian Sugianto; Nurul Hermina (Greenation International Journal of Tourism and Management, 2026)
International cooperation projects funded by multilateral development institutions such as the Islamic Development Bank, World Bank, and Asian Development Bank require high standards of accountability, compliance, and performance. In the Indonesian health sector, the implementation of foreign funded projects faces various challenges, including differences in budget absorption rates, administrative complexity, and human resource turnover. These conditions indicate that project success is not determined solely by funding availability and governance systems but is also influenced by the quality of human resources involved in project implementation. This study aims to analyze the effect of Human Resource Competence and Organizational Commitment on the performance of international cooperation projects at the Directorate General of Advanced Healthcare, Ministry of Health of the Republic of Indonesia. A quantitative research approach was employed using a survey method. Data were collected from 75 respondents who were directly involved in the management of international cooperation projects through purposive sampling. The data were analyzed using multiple linear regression with the assistance of IBM SPSS Statistics 27. The findings reveal that Human Resource Competence has a positive and significant effect on Project Performance, indicating that technical, managerial, and behavioral competencies contribute substantially to project effectiveness. Organizational Commitment demonstrates a positive but statistically insignificant partial effect on Project Performance. However, Human Resource Competence and Organizational Commitment simultaneously have a significant influence on Project Performance. The study highlights the strategic importance of competency development in improving project outcomes, compliance with donor requirements, and organizational effectiveness. The findings provide practical implications for policymakers and project managers in strengthening human resource capacity through training, certification, knowledge transfer, and continuous professional development to enhance the success of international cooperation projects.